ANALYSIS OF EFFICIENCY OF PHARMACEUTICAL COMPANIES IN SERBIA BASED ON THE CODAS METHOD - Lukić, Radojko (Poslovna ekonomija, 2022)
Recently, as it is known, the performance (efficiency) of pharmaceutical companies is increasingly measured on the basis of multi-criteria analysis. With this in mind, this paper analyzes the efficiency of pharmaceutical companies (engaged in the production and distribution or only distribution of pharmaceutical products) in Serbia on the basis of the CODAS method. In this context, adequate measures have been proposed to improve the efficiency of pharmaceutical companies in Serbia in the future. The obtained results of the analysis of the efficiency of the observed pharmaceutical companies in Serbia on the basis of the CODAS method show that the most efficient pharmaceutical company is Hemofar. Then in order are: Novo Nordisk, Roshe, Phoenix Pharma, Pfizer, Krka, Galenika, Velexfarm, Vega, Zdravlje, Pharmanova, Pharma Swiss, i Farmalogist.This positioning of pharmaceutical companies in terms of efficiency in Serbia has been influenced by numerous macro and micro factors, such as: economic climate, living standards, research and development expenditures, political stability, digitalization of business, and others.